Players’ Rehabilitation and Reeducation Between Electro Stimulation Methods and Classical Work - HADJIDJ, Mouloud; MAHOUR BACHA, Sabira (Journal of Human Sciences, 2018)
Numbers of athletes keep on playing despite a tendinitis and, as a result, the injury quickly becomes more serious and may even evolve into a chronic tendinopathy. These reasons explain why the technical staff should be very attentive and not hesitate to put the athlete to rest in order to avoid the appearance of tendinopathies. The medical staff generally asks for an ultrasound scan to be able to observe the peritendinous effusion. The athlete, in some cases, needs surgery which success is guaranteed but the reeducation is lengthy. The medical staff should implement a precise program, the reeducation should be specific and minutely followed, and the fitness trainer will work closely with the athlete to allow him to regain all his high level capacities and qualities. One speaks of rehabilitation period during which the medical staff and the fitness trainer should collaborate to analyze the player’s evolution and decide whether he should resume collective training. A bad reeducation and rehabilitation will lead to a risk of an omnipresent relapse.